The Emergence of Free Will and Predestination: Genealogical Studies in History of Early Islamic Thought - Sidik, Muhammad Alfan; Sarwanto, Sarwanto (Regalia Institute, 2024)
This article focuses on the emergence of the idea of free will and predestination in history of early Islamic Thought and the factors that influence its emergence. This research uses a historical analysis approach, this approach involves several important steps, such as heuristics, source criticism (both internal and external), interpretation, and historiography. The results of this research show that there are various actors who influence its emergence so that it narrows down in several groups that appear in Early Islamic history such as Khawarij, Jabariya, Qadariya. Mu’tazila and Ashariya. This article also looks at the emergence of the thought of free will and predestination from the influence of pre-Islamic Arab thought and political conditions and also the influence of outside Arab thought.